Approaches to private participation in water services : a toolkit - Public-Private Infrastructure Advisory Facility; World Bank. (Washington, DC : International Bank for Reconstruction and Development/World Bank, 2006)
Provides options for the design of policies to facilitate the delivery of good quality water and sanitation services to the poor. It highlights the need for tariffs, investment, stakeholder consultation, and regulatory policies to address the affordability and sustainability of those services.
Includes bibliographical references (p. 277-301) and index.
oif 16/09/15
Loan
Keywords: Water-supply -- Economic aspects -- Developing countries; Water-supply -- Government policy -- Developing countries; Sanitation -- Economic aspects -- Developing countries; Sanitation -- Government policy -- Developing countries; Public-private sector cooperation -- Developing countries